Sustainability and financial implications of the Labour Relations Amendment Act No.6 of 2014 for Western Cape health services outsourcing - Lucas, Jonathan Winston (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.